Formulation of Snack Bar Based on White Mussel as TFA (Therapeutic Food for Anemia) To Improve Adolescents Nutrition - Arie Dwi Alristina; Rizky Dzariyani Laili; Luki Mundiastuti; Dewinta Hayudanti; Rossa Kurnia Ethasari (University of Sultan Ageng Tirtayasa, 2023)
The purpose of this study is to enhance adolescent nutrition, specifically anemia and stunting, in accordance with the National Research Master Plan's public health and nutrition theme. In order to break the chain of stunting, giving TFA (Therapeutic Food for Anemia) to adolescent females at school is one of the measures taken. This study employed four formulation groups (P1) 0:80:20; (P2) 15:65:20; (P3) 25:55:20; (P4) 35:45:20 (White Mussel Powder: Moringa Flour: Brown Rice Flour) to create the refreshment bar. This study's objective was to evaluate the TFA food formula based on organoleptic and nutrient content tests prior to administering it to panelists. This is experimental research in the form of a formulation of a local seafood product with white mussel (Corbula faba Hinds) as the primary ingredient. The obtained data were then analyzed using ANOVA (Analysis of Variance) to determine which TFA formula was the panelist team's organoleptic preference. The P4 formulation contained the maximum levels of protein (11.31%) and iron (87.42 mg/100 g), as determined by the results. In addition, the organoleptic test revealed that formulation P3 was the most preferred treatment. In conclusion, TFA with formulation P3 can be used to enhance the nutrition of adolescents.